Ethnobotanical Study of Traditional Medicinal Plants Used for the Treatment of Infectious Diseases by Local Communities in Traditional Authority (T/A) Mbelwa, Mzimba District, Northern Region, Malawi - Wilfred A. Chisamile; Mubo A. Sonibare; John F. Kamanula (J, 2023)
Local communities in Mzimba District, Malawi, have limited access to healthcare services and often rely on traditional medical practice and medicinal plants (MPs) for most of their medical care. However, phytomedicines’ use has not been well documented. This study aimed to identify and document medicinal plants and the associated ethnobotanical knowledge. Ethnobotanical data were collected in seven localities (19 villages) in the T/A Mbelwa, Mzimba, from May to June 2021. Forty traditional healers, herbalists, and farmers selected purposively and by snowball sampling were interviewed through semi-structured interviews, field observations, group discussions, and guided field walks. Quantitative indices, viz. relative frequency of citation (RFC), use value (UV), relative importance (RI) values, informant consensus factors (ICFs), and fidelity levels (FLs), were used to analyze the data. Eighty MPs belonging to 43 families and 77 genera were recorded. The Leguminosae family showed the highest number of species (16), followed by Solanaceae, Rubiaceae, and Phyllanthaceae. Trees (35 species) and roots (62%) accounted for the most significant habit and part, respectively. Washing (29%) was the most common preparation method. The most cited plant was Zanthoxylum chalybeum (RFC = 0.80, UV = 0.28, RI = 1.66), followed by Cassia abbreviata (RFC = 0.68, UV = 0.35, RI = 1.50). Respiratory disorders showed the highest ICF (0.53), followed by general and unspecified disorders (0.31). Z. chalybeum, C. abbreviata, and Oldfieldia dactylophylla showed maximum FLs (100%) for treating malaria and dysentery. Phytochemical, bioassay, toxicity, and conservation studies are needed to assess medicinal plants’ safety, efficacy, and quality as steps toward discovering new promising therapeutic leads without neglecting conservation programs for their sustainable utilization.